Probabilistic classification criterion for failure modes of reinforced concrete columns - Yu, Bo (2022)
A probabilistic classification criterion was proposed to classify likely failure modes of reinforced concrete (RC) columns under seismic loading conditions. The accuracy and applicability of available flexure and shear strength models were scrutinized first to calculate the ratio of shear demand to shear strength (m). Then the probabilistic distribution characteristics of m, shear aspect ratio (λ), and transverse reinforcement ratio (ρ sv) were examined to determine the probability of RC columns failing in different failure modes. Subsequently, a probabilistic classification criterion for likely failure modes of RC columns was suggested by considering the coupling effects of m, λ and ρ sv. Finally, the classification accuracy of the proposed classification criterion was corroborated by comparing with existing classification criteria. Results reveal that the classification accuracy of the proposed probabilistic criterion is about 20% higher than those of existing classification criteria for RC columns failing in flexure, flexure-shear, and shear critical modes. The failure modes of RC columns progressively change from ductile flexure failure to flexure-shear, and then shear critical failure mode with the increase of m, and the decrease of λ and ρ sv.